2003
DOI: 10.1152/japplphysiol.00599.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide on exercise-induced proteinuria in rats

Abstract: Gü ndü z, Filiz, Oktay Kuru, and Ü mit Kemal S entü rk. Effect of nitric oxide on exercise-induced proteinuria in rats. J Appl Physiol 95: 1867-1872, 2003. First published July 18, 2003 10.1152/japplphysiol.00599.2003.-Temporary proteinuria occurring after exercise is a common finding, and it is explained predominantly by alterations in renal hemodynamics. In this study, we investigated whether nitric oxide (NO), which is known to have an effect on renal hemodynamics and to increase during exercise, has a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…The results of these measures are consistent with the data reported for the same experimental 5/6Nx model [1], [3], [12], [17], [22]. The decrease in proteinuria after EXE may be related to the output of nitric oxide [32], prostaglandins and histamine, which all contributed to the pressure decrease after the training period [33]. In our laboratory, Bergamaschi et al showed that treadmill exercise (65% to 75% vO 2 max) for 30 min, 5 times/week for 60 days in Munich-Wistar rats with 5/6Nx [3] reduced the total glomerular filtration rate and decreased the proteinuria and glomerulosclerosis indices.…”
Section: Discussionsupporting
confidence: 90%
“…The results of these measures are consistent with the data reported for the same experimental 5/6Nx model [1], [3], [12], [17], [22]. The decrease in proteinuria after EXE may be related to the output of nitric oxide [32], prostaglandins and histamine, which all contributed to the pressure decrease after the training period [33]. In our laboratory, Bergamaschi et al showed that treadmill exercise (65% to 75% vO 2 max) for 30 min, 5 times/week for 60 days in Munich-Wistar rats with 5/6Nx [3] reduced the total glomerular filtration rate and decreased the proteinuria and glomerulosclerosis indices.…”
Section: Discussionsupporting
confidence: 90%
“…Besides muscle damage reactive oxygen species also have harmful effects on several tissues such as the heart, kidney, cerebrum, liver [9] and erythrocytes, as shown in our previous studies [11, 12]. We proposed a causal relationship in our previous study between exercise-induced oxidant stress and exercise-induced proteinuria in rats [13]. Exhaustive treadmill exercise in sedentary rats caused exercise-induced proteinuria as expected.…”
Section: Introductionmentioning
confidence: 55%
“…Proteinuria is a widely reported side effect that occurs after VEGF signaling is inhibited, and it may reflect severe glomerular damage [24]. The pathogenesis of proteinuria in patients receiving anti-VEGF therapy likely relates to multiple pathways, including post-exercise proteinuria-like syndrome [25], the perturbation of podocyte-endothelial VEGF axis signaling [26] [27], podocyte protein junction downregulation [28], and subacute glomerular thrombotic microangiopathy [24]. On the other hand, no major differences were found between Asian and Caucasian people in relation to axitinib plasma pharmacokinetics during the phase I pharmacokinetic studies [29] [30].…”
Section: Discussionmentioning
confidence: 99%